(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This thesis systematically highlights the civil law nature of the motor transport logistics services contract, its differences from contracts for freight transportation, transport forwarding, paid services, and warehousing (storage). In the practice of Uzbekistan, the so-called "logistics service" often combines such functions as transportation, forwarding, storage, packaging, marking, information exchange, and tracking within the framework of one contract; therefore, it should be legally substantiated as a "complex/mixed contract." This approach is based on the concept of freedom of contract and a mixed contract of the Civil Code of Uzbekistan and is reinforced by a comparative analysis with the criteria typengemischter Vertrag and "Schwerpunkt" (priority goal) in German law, the dominant purpose test in the USA. Also, a "single module-contract model" is proposed for the evidentiary significance of CMR and e-CMR documentation in international road transport, the distribution of responsibility by module, and the clear definition of regression (subrogation) mechanisms in the contract.